Chemical and the Acceptability of Chicken Nuggets as Functional Food with Utilization Rice Bran to Substitute Wheat Flour - C. Maliluan -; Y. B. Pramono -; B. Dwiloka - (Universitas Muhammadiyah Semarang, 2013)
The purpose of this research was produce a product with the chemical properties and acceptability as well as having health benefits. The research was conducted from July to September 20 12. The variables in this research were insoluble dietary fiber, antioxidant activity, and sensory test. Dietary fiber was measured using the total multienzyme method, antioxidant activity was measured using DPPH method and the acceptability for the sensory test. Completely Randomized Design (CRD) with 4 treatments and 5 replications were used in this research. Treatment in this research was the total substitution of rice bran (w / w), consisting of : T0 = 0%, T1 = 25%, T 2 = 50%, T 3 = 75%, T4 = 100. The data obtained were further processed by analysis of variance to determine the effect of treatment. If there was any significant effect of treatment then it was followed by Duncan’s Multiple Range Test to determine the differences among the treatments. Based on the results of the study showed that the use of rice bran increase insoluble dietary fiber. Similarly, the antioxidant activity, the higher utilization of rice bran, significantly (P <0.05) increased the antioxidant activity of rice bran chicken nuggets. Overall, the use of rice bran as a substitute for wheat flour can improve the chemical properties but lower the acceptability of chicken nuggets as functional food.